Computed tomographic analysis of hemifacial spasm: narrowing of the posterior fossa as a possible facilitating factor for neurovascular compression. - Kamiguchi, H (1997)
Hemifacial spasm can be caused by vascular compression of the facial nerve at the root exit zone from the brainstem. Several case reports suggest that narrowing of the cerebellopontine angle cistern caused by Paget's disease, abnormal elevation of the petrous bone caused by hyperplasia, or contralateral acoustic neurinoma may increase the chance of vascular compression of the facial nerve. Therefore, posterior fossa narrowness has been evaluated in 34 patients with hemifacial spasm by measuring the petrous angle and pons diameter index to elucidate whether narrowing of the posterior fossa can act as a facilitating factor for neurovascular compression. The petrous angle in the hemifacial spasm group was significantly smaller than that in the control group, which consisted of 33 patients with an unruptured supratentorial aneurysm, and the pons diameter index in the hemifacial spasm group was significantly greater than that in the control group. These results indicate that the cerebellopontine angle cistern of patients with hemifacial spasm is narrower resulting in more crowded cranial nerves and vascular structures compared with patients without hemifacial spasm. The narrowness of the cerebellopontine angle cistern may be a possible factor in facilitating neurovascular compression in hemifacial spasm.